Pengaruh Karakteristik Perusahaan Terhadap Kualitas Laporan Keuangan(Study Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2013) - Puji Astuti, Yunita; , Dr. Triyono, S.E., M. Si (2015)
The research aimed to analyze the effect of firm characteristics on the quality of financial reporting on companies listid on the Indonesian Stock Exchange. The data used in this study were 173 companies manufacturing a listing on the Indonesia Stock Exchange during the period 2010-2013. Data analysis techniquein this research is multiple linear regression analysis with the help of this research program SPSS. The result showed that the coefficient of determination obtained a value of 37,7% of financial reporting quality is influenced by the characteristics of the company consisting of leverage, liquidity, profitability, size, and age, the remaining portion of 62,3% is affected by variables outside of the model. F-test of 21,807>2,27 and 0,000 significant which means that the model used in the research is fit. The result of this research indicate that leverage, liquidity, profitability, showed significant result while size and age showed no significant result on quality of financial reporting